Treatment of a thyroglossal duct fistula using the modified Sistrunk technique: A case report (Research, Society and Development, 2025)
During the intrauterine phase, embryological structures such as the branchial arches develop, resulting in structures like the pharyngeal diverticulum, which will later give rise to the thyroid gland and the thyroglossal duct, both vital for human development. However, malformation of these structures can give rise to cysts and fistulas along the thyroglossal duct, resulting in difficulties in moving the tongue, dysphagia, or dysarthria. To treat this pathology, surgical intervention is required, based on the Sistrunk technique, which aims to remove the cysts and fistulas associated with the thyroglossal duct, as well as all its fistular epithelium or cystic capsule, with a safety margin to avoid a recurrent process. This manuscript aims to report a clinical case of a male patient, aged 1 year and 8 months, who had a fistula arising from the thyroglossal duct on the dorsum of the tongue without a path of continuity, resulting in a cleft tongue. The patient was seen at the “Santa Casa de Misericórdia” hospital in Araçatuba City for surgical removal of the lesion associated with the tongue with a safety margin, and it was possible to completely resolve the case, confirmed by the three-month follow-up of the patient, who currently has a completely healed surgical site and control of tongue movement, speech and swallowing. We, therefore, conclude that the more conservative surgical approach, using the modified Sistrunk technique, proved to be effective in this case, promoting the return of function and complete healing of the wound without any recurrences or intercurrences.